The Great Economic Crisis in Poland (1929–1935) in the Context of the Global Crisis - Klimiuk, Zbigniew (Historia i Polityka, 2022)
The aim of the article was to analyze the causes and consequences of the great economic crisis in Poland in the context of the world economy and the global crisis. The first symptoms of the crisis became evident in June 1929, when production began to decline, and in August that year price drop began. After these events, the economic situation in Poland was systematically deteriorating. The year 1935 can be considered the end of the crisis in Poland, despite the fact that the industrial crisis began to break through gradually already in 1933. The great economic crisis was a global phenomenon, even though it did not start in all countries at the same time. It depended on the internal economic situation of each of them. It stood out against the background of previous economic crises due to the fact that only the introduction of state interventionism in the form of the “New Deal” program in the USA brought about an improvement in the situation, and therefore, in 1933, some economic recovery began in the world. However, in some parts of the world (including Poland), due to the specific features of their economies, the crisis lasted until 1935. The crisis of 1929–1935 was rightly called “the great crisis”, not only because of economic problems, but also due to political consequences, i.e., the strengthening of totalitarian systems in Western Europe and the growing importance of the communist movement around the world (the USSR was the only country not affected by its consequences). The great economic crisis was characterized by: longevity – in industrial countries it lasted until 1933, and in agricultural countries until 1935; depth of impact – it covered all areas of the economy: industry, agriculture, domestic and foreign trade, transport, monetary and credit system; wide geographic scope – it covered all countries of the world connected with the world capitalist system and capitalist economies; the scale of the decline in economic growth rates – in the history of economic crises to date, the world economy has not experienced such a deep collapse and stagnation.